Imperfections and Intimacies: Trebling Effects and the Improvisational Aesthetics of Pandemic-Era Livestreaming - Risk, Laura (Critical Studies in Improvisation / Études critiques en improvisation)

(untitled) (University of Guelph College of Arts, 2021)
This article develops the concept of an improvisational aesthetic of imperfection and intimacy for “trebling-effect” music livestreams, or webcasts where listeners may interact with each other (and possibly with the performer) during the stream via text chat. I position the pandemic-era turn towards livestreaming within scholarly discourses of “liveness” and in conversation with recent work on the impact of audio streaming platforms on listeners’ understandings of the functionality of music. I also consider the affective labour required of performers to generate a sense of human connection via livestream, and discuss video mosaics, by which musicians separated by time and space perform together in an illusion of copresence. I conclude with a case study of the #CanadaPerforms livestreaming series, a public-private collaboration between the National Arts Centre and Facebook Canada.